Nutritional Status Profile of Women of Reproductive Age Based on Anthropometric Indicators - Juan Christianto Karuhgair; Rifatolistia Tampubolon; Gelora Mangalik (Indonesian Journal of Global Health Research, 2025)
Nutritional status reflects the balance between nutritional needs and intake, which is crucial for the health of women of reproductive age, as it directly affects reproductive function, pregnancy, and overall family well-being. This study aimed to accurately assess their nutritional status using anthropometric indicators as an initial step to prevent metabolic disease risks in women of reproductive age. This was a descriptive study with a cross-sectional design conducted from November 2024 to January 2025. The population consisted of all women of reproductive age (WRA) with total of 45 respondents were selected using purposive sampling. Data were collected through direct observation using a checklist that included demographic characteristics and anthropometric measurements. The data were analyzed univariately and classified based on WHO standards to determine categories of undernutrition, normal, overweight, and central obesity. Results were presented in tables, charts, and descriptive narratives. Most women of reproductive age (WRA) were in the productive age range of 21–35 years, with the majority having a senior high school education and working as employees or laborers. Nutritional status, based on BMI and MUAC, was predominantly in the normal category; however, waist circumference and waist-to-hip ratio (WHR) measurements indicated a high prevalence of central obesity among the WRA. All respondents had a WHR ≥ 0.85, indicating a high risk of non-communicable diseases such as hypertension and type 2 diabetes. This study assessed the nutritional status of women of reproductive age using anthropometric indicators such as BMI, MUAC, waist circumference, and WHR. While most had normal nutritional status, there was a high prevalence of central obesity, which poses a risk for non-communicable diseases like hypertension and diabetes.